Pengaruh Naturalistic Intelligence dan New Environmental Paradigm terhadap Environmental Sensitivity - Lisa Dwi Ningtyas (Universitas Negeri Jakarta, 2019)
Globalization currently developing with very rapidly. The negative impact of the rapid development of globalization is environmental damage. One of the necessary to prevent damage to the environment that is environmental sensitivity on the self every students. That’s the destination holding of this research, which is to find whether there is effect of naturalistic intelligence and new environmental paradigm toward students’ environmental sensitivity. This research involving 91 students in Jakarta as a sample of random selected. There are 3 instruments has been developed to measure these variables. Each of the instruments has reliability .824, .583, and .579. Data has been analyzed by path analysis. The result of the research indicate that there is a significant effect between new environmental paradigm toward students’ environmental sensitivity (.436). But, in this research it was’nt proven naturalistic intelligence contribute significantly toward students’ new environmental paradigm or students’ environmental sensitivity. so that, new environmental paradigm is not proven as a mediator variable that significantly mediates between naturalistic intelligence and students’ environmental sensitivity. Therefore, in the increases students’ environmental sensitivity , factor such as new environmental paradigm can be considered.